KELEMBAGAAN DAN SALURAN PEMASARAN SAGU DI KABUPATEN BURU: (Sago Institutions and Marketing Channels in Buru Regency) - Bahasoan, Husen (Uniqbu Journal of Exact Sciences, 2022)
Sago as a staple food in Maluku has several comparative advantages compared to other foodstuffs. The purpose of the study was to determine the marketing and institutional efficiency of sago in Buru Regency. The method used is to measure the share of the price received by sago processing farmers by using a marketing margin and to determine the share of the price received by sago processing farmers. that the percentage received by sago farmers in Waetina Village is much higher than in other villages, namely 92 percent. The highest marketing margin is in Waetele Village and the most efficient marketing margin is in Waetina Village. The marketing profit of sago farmers in Waetele Village and Waegeren Village is higher than that of Waelo Village and Waetina Village. The three components of the institutional analysis applied are the analysis of institutional arrangements; institutional and organizational performance; and characteristics of successful sago management institutional arrangements.